Who are the green innovation pacesetters? Local or non-local executives - Lei Zhu; Qianwen Zheng (China Journal of Accounting Studies)
This study examines how senior executives’ hometown identity affects corporate green innovation. We find that firms led by local executives invest less in green innovation than those led by non-local executives. This trend is particularly more pronounced when the executive serves as the board chairman, in regions with more active supervision from the local public, and in regions with lower marketisation levels. Notably, stronger local government environmental oversight does not mitigate this negative relationship. Further analysis shows that firms with local executives are less likely to face environmental penalties and more likely to receive environmental subsidies. Moreover, green innovation investment has no significant effect on financial performance or environmental expenditures. These results remain robust under alternative model specifications and variable definitions. Overall, the findings support the resource effect hypothesis and suggest that hometown ties allow local executives to reduce green innovation efforts under greater local tolerance.